Bees & butterflies: Polish migrants' social anchoring, mobility and risks post-Brexit. Issue 13 (2nd July 2020) - Trąbka, Agnieszka; Pustulka, Paula
ABSTRACT: The result of the Brexit referendum and subsequent uncertainty regarding its actual consequences, particularly for the EU citizens living in the UK, constitutes a major point of reference and a social risk for many Polish migrants. Drawing on two qualitative research projects with a data set of 71 semi-structured interviews, this paper aims at analysing post-Brexit strategies of Polish migrants in Britain, taking into account their anchoring and embedding, their attitudes towards mobility, and the specificity of perceived risks. The main objective is to offer a data-driven and temporally agile typology of the orientations migrants adopt in the face of uncertainty. With four ideal types of bumblebees, honeybees, butterflies and cocoons, we capture both the diversification of people's reactions and strategies, and possible directionalities of the changes in their mobility and social anchoring over time.